2001
DOI: 10.1002/ajpa.10010
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability of West New Guinea populations

Abstract: This paper reports human mitochondrial DNA variability in West New Guinea (the least known, western side of the island of New Guinea), not yet described from a molecular perspective. The study was carried out on 202 subjects from 12 ethnic groups, belonging to six different Papuan language families, representative of both mountain and coastal plain areas. Mitochondrial DNA hypervariable region 1 (HVS 1) and the presence of the 9-bp deletion (intergenic region COII-tRNA(Lys)) were investigated. HVS 1 sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 67 publications
1
53
0
Order By: Relevance
“…For comparison, the gross frequencies of these haplogroups as observed in other regions of Asia/Oceania, pooled from different population samples, are included as well using previously published data. 7,10,16,18,42 For practical reasons, the PNG Highlands group includes Kapuna, a Papuan-speaking group from the Gulf Province of PNG with an assumed origin in the highlands, while the PNG Coast group includes Bereina, an Austronesian-speaking group from the southern coastal area of PNG. Figure S1) indeed showed that its haplotypes are quite diverse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For comparison, the gross frequencies of these haplogroups as observed in other regions of Asia/Oceania, pooled from different population samples, are included as well using previously published data. 7,10,16,18,42 For practical reasons, the PNG Highlands group includes Kapuna, a Papuan-speaking group from the Gulf Province of PNG with an assumed origin in the highlands, while the PNG Coast group includes Bereina, an Austronesian-speaking group from the southern coastal area of PNG. Figure S1) indeed showed that its haplotypes are quite diverse.…”
Section: Discussionmentioning
confidence: 99%
“…For comparisons in a wider geographic context, we included previously described population data from East Asia, Island Southeast Asia, and Near and Remote Oceania, using a minimal sample size of 20 individuals per population for both NRY and mtDNA 7,10,16,18,42,43 (for an overview, see Supplementary Table S1). …”
Section: Materials and Methods Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Population demographic simulations also referred to other significant population exchange/movements, as the mtDNA- Haplogroup prediction of ancient samples are given with letters in bold after their names. mitCRS, rCRS; Derenburg, Derenburg 1 specimen from Germany; 6 Stone Age Eulau, Eulau sequence from the Later Stone Age Corded Ware Culture, Germany; 31 Guinea, recent New Guinea sequence; 32 North Indian, recent North Indian sequence; 33 Philippines, recent Philippine sequence; 34 Siberian, Siberian specimen; 5 Iberian, Iberian specimen. 7 (b) In this dendrogram for European Neolithic mtDNA sequences, the overlapping regions between nt16055 and nt16378 were considered for alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Sea dwellers who bore the Lapita culture introduced the Austronesian language as well as their genetic traits into this region about 3,500 years ago (Bellwood 1989). A recent study on mitochondrial DNA suggested that the Dani and the Asmat shared a common Papuan ancestor (Timmaseo-Ponzetta et al 2002); however, the B3D27 was found in the Asmat but not in the Dani. Austronesian infiltration into New Guinea has genetically been demonstrated in the Asmat and the Gidra as well as in the populations inhabiting nearby islands, but not in the Dani (Ohashi et al, 2000;Nakayama et al unpublished data).…”
Section: Discussionmentioning
confidence: 95%